The effect of mephedrone and caffeine, and the influence of WAY-100635 on c-fos expression in the rat brain - Adam, Lucy (2022)
Mephedrone is a commonly abused drug, with recreational users comparing its effects to MDMA. Polydrug use of mephedrone has been widely documented and forensic analysis has identified caffeine as key drug that is co-consumed. The current study aimed to identify the changes in c-fos expression, a commonly used marker in research to determine neuronal stimulation in response to mephedrone and caffeine administration, and the effect that inhibition of the 5-HT1A receptor has on this expression.